(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Compensation, in layman’s terms, refers to something provided or obtained as payment or reparation, such as property, for a service or loss. The word Reward, on the other hand, refers to something offered or earned as a reward for good behaviour or as a form of retaliation for bad behaviour. In this context, the current paper focuses on wage management as a means of balancing employee relationships. The study is conducted by taking 199 employees of selected retail industry. The data has been collected by administering a structured questionnaire and analysis is done using regression analysis.